ARTWORK BOARD GAME “MY PET” SEBAGAI MEDIA PENGENALAN TANGGUNG JAWAB PADA ANAK - Maximilianus Novaryant; Jasson Prestiliano; Peni Pratiwi; T. Arie Setiawan Prasida (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2024)
AbstractArtwork Board Game "My Pet" as an Introduction to Children’s Responsibility. Pets can be good friends for children, but it is important to teach children how to be responsible for their pets. In the board game, there is one element that is important for the smooth delivery of the board game message, namely the visual artwork element. “My Pet” board game is a game designed with artwork to educate children about the responsibility of their pets. The method used in this research is a mixed method with the strategy used being cyclic. The “My Pet” board game artwork is implemented and arranged in such a way based on the visual perception and visual tastes of children 7-8 years old so that the board game is attractive, interactive, communicative, and the information message on the board game can be received properly and clearly by children. The design result is made into a prototype and then continues to the board game artwork testing stage. From this research, it can be concluded that board game artwork which is designed by taking into account the visual perception and visual tastes of the target audience, in this case, children aged 7-8 years, can help children understand the content of the message the board game wants to convey, namely introducing children to responsibility in taking care of his pets.Keywords: pets, board game, visual artwork, illustration, children AbstrakArtwork Board Game “My Pet” Sebagai Media Pengenalan Tanggung Jawab pada Anak. Hewan peliharaan dapat menjadi teman yang baik bagi anak-anak, tetapi penting untuk mengajarkan anak bagaimana bertanggung jawab terhadap hewan peliharaannya. Pada board game ada salah satu elemen yang penting bagi kelancaran penyampaian pesan board game yaitu elemen visual artwork. Board game “My Pet” adalah game yang dirancang dengan artwork untuk mengedukasi anak tanggung jawab pada hewan peliharaannya. Metode yang digunakan dalam penelitian ini yaitu menggunakan metode mixed method dengan strategi yang digunakan yaitu cyclic. Artwork board game My Pet diimplementasikan dan diatur sedemikian rupa dengan berdasarkan persepsi visual dan selera visual anak 7-8 tahun agar board game menarik, interaktif, komunikatif, dan pesan informasi pada board game dapat diterima dengan baik dan jelas oleh anak. Hasil perancangan dibuat menjadi prototype yang kemudian dilanjutkan ke tahap pengujian artwork board game. Dari penelitian ini didapatkan simpulan bahwa artwork board game yang dirancang dengan memperhatikan bagaimana persepsi visual dan selera visual target audience dalam kasus ini anak usia 7-8 tahun, dapat membantu anak dalam memahami isi pesan yang ingin disampaikan oleh board game yaitu mengenalkan anak tanggung jawab dalam merawat hewan peliharaannya.Kata kunci: hewan peliharaan, permainan papan, karya seni visual, ilustrasi, anak